Development of Adaptability and Value Orientations of Kazakh Students in the course of Sociocultural Adaptation - Z V Boyko; L B Husenova (Peoples' Friendship University of Russia (RUDN University), 2011)
The article is devoted to the analysis of the results of research of adaptability and value orientations in students from Kazakhstan. The peculiarities of adaptability and value orientations of the first and fourth courses Kazakh students in their first and fourth years at university, living in Russia, are compared in the article.